2019
DOI: 10.1364/boe.10.002639
|View full text |Cite
|
Sign up to set email alerts
|

Joint retina segmentation and classification for early glaucoma diagnosis

Abstract: We propose a joint segmentation and classification deep model for early glaucoma diagnosis using retina imaging with optical coherence tomography (OCT). Our motivation roots in the observation that ophthalmologists make the clinical decision by analyzing the retinal nerve fiber layer (RNFL) from OCT images. To simulate this process, we propose a novel deep model that joins the retinal layer segmentation and glaucoma classification. Our model consists of three parts. First, the segmentation network simultaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 34 publications
0
37
0
Order By: Relevance
“… 9 14 More recently, machine learning and deep learning methods have been used, including support vector machines, 15 , 16 random forest classifiers, 17 patch-based classification with convolutional neural networks 18 22 or recurrent neural networks, 20 , 22 semantic segmentation with fully convolutional (encoder–decoder) networks, 22 26 and other deep learning methods. 27 30 Importantly, some of these methods have been applied to OCT images from patients with age-related macular degeneration, 18 , 20 , 24 , 27 diabetic retinopathy, 11 , 25 macular telangiectasia type 2, 29 diabetic macular oedema, 13 , 23 , 24 pigment epithelium detachment, 28 glaucoma, 15 , 30 multiple sclerosis 17 , 26 retinitis pigmentosa, 31 and neurodegenerative diseases. 32 These diseases are characterized by variable thinning of the inner retinal layers (e.g., glaucoma and multiple sclerosis), thickening or cystic changes in the nuclear layers (e.g., macular telangiectasia type 2 and diabetic retinopathy) or focal disruption of the retinal pigment epithelium (RPE, e.g., age-related macular degeneration, macular telangiectasia, and pigment epithelium detachment).…”
Section: Introductionmentioning
confidence: 99%
“… 9 14 More recently, machine learning and deep learning methods have been used, including support vector machines, 15 , 16 random forest classifiers, 17 patch-based classification with convolutional neural networks 18 22 or recurrent neural networks, 20 , 22 semantic segmentation with fully convolutional (encoder–decoder) networks, 22 26 and other deep learning methods. 27 30 Importantly, some of these methods have been applied to OCT images from patients with age-related macular degeneration, 18 , 20 , 24 , 27 diabetic retinopathy, 11 , 25 macular telangiectasia type 2, 29 diabetic macular oedema, 13 , 23 , 24 pigment epithelium detachment, 28 glaucoma, 15 , 30 multiple sclerosis 17 , 26 retinitis pigmentosa, 31 and neurodegenerative diseases. 32 These diseases are characterized by variable thinning of the inner retinal layers (e.g., glaucoma and multiple sclerosis), thickening or cystic changes in the nuclear layers (e.g., macular telangiectasia type 2 and diabetic retinopathy) or focal disruption of the retinal pigment epithelium (RPE, e.g., age-related macular degeneration, macular telangiectasia, and pigment epithelium detachment).…”
Section: Introductionmentioning
confidence: 99%
“…The first U-net segments the several layers whereas the second one refines possible errors in the prediction, thus generating strict topologically correct segmentations [32]. Similar strategy is also presented in Wang's research, which introduces a post processing network to enforce the topology correctness [24]. The topological correction ability of these methods relies on specifically designed cost functions [30,31] or additional post-processing networks [24,32].…”
Section: Introductionmentioning
confidence: 93%
“…Although the segmentation results are promising, such methods usually suffer from large redundancy and result in more inference time [22]. A more elegant framework is pixel classifying by the fully convolutional network (FCN) [23,24]. This kind of method takes advantage of convolutional networks and uses an encoder-decoder architecture to assign each pixel to a label.…”
Section: Introductionmentioning
confidence: 99%
“…Venhuizen et al implemented retinal thickness measurement and intraretinal cystoid fluid quantification based on U-shape FCN architecture [31]. Researchers have demonstrated that the second strategy possesses state-of-the-art performance on pixel-wise labeling [22], [23], [32] in biomedical image segmentation with limited training set. As a result, this strategy is also employed in the current work.…”
Section: Introductionmentioning
confidence: 99%